Education and Training of Women - Saloma-Akpedonu, Czarina (Archīum Ateneo, 2020)
The national landscape of education and training in the Philippines has witnessed significant changes since the publication of the Philippine NGO Beijing+20 Report in 2015. However; a disruptive reality of risks and disasters neutralize these education reforms. An average of 20 weather-related disturbances yearly and armed conflicts resulted in more frequent population displacements in the country. Furthermore; state-led and capitalist development such as urban renewal projects; public infrastructure; and commercial ventures are causing population dislocation in big cities. Moreover; questions of access and representativeness in terms of diversification of student bodies (e.g.; entry of non-traditional students from indigenous people communities; adult learners) and quality (e.g.; performance in international assessment programs of basic education; world university rankings) remain. Against the backdrop of specific opportunities and challenges; this stocktaking of the gaps and gains in the critical area of education and training of girls and women in the country focuses on the efforts of government and civil society organizations in attaining the Strategic Objectives of the Beijing Platform for Action.